Waqf Accounting in Indonesia and Malaysia : an Approach Systematic Literature Review - Adeva Rizky Yudithia; Erfan Erfiansyah; Aira Farhana binti Zulkarnian; Masniza Binti Supar (Greenation Research & Yayasan Global Resarch National, 2025)
Indonesia and Malaysia, as two Muslim-majority countries in Southeast Asia, have great concern for the management of waqf. Both have developed a waqf accounting system with different approaches in accordance with their respective local regulations and practices.This study aims to conduct a systematic review of the development of waqf accounting practices in Indonesia and Malaysia. This method uses Systematic Literature Review (SLR) with the PRISMA approach. Of the 224 articles identified through database Scopus, Garuda, and Google Scholar, as many as 28 articles that met the criteria and were further analyzed. The results show that Indonesia adopted PSAK 112 which has now changed to PSAK 412 as a waqf accounting standard, while Malaysia uses a decentralized approach controlled by the State Islamic Religious Council (MAIN). The results of the analysis show that the two countries have different approaches in reporting and managing waqf, both in terms of regulations, institutional roles, and the use of technology. This study provides a new understanding of the challenges in aligning waqf accounting standards as well as the importance of increasing the capacity of nazhir to realize accountable and sustainable waqf management at the global level.